Current State of Contamination by Persistent Organic Pollutants and Trace Elements on Piabanha River Basin - Rio de Janeiro, Brazil - de Mello, Flávia Vasconcelos; de Carvalho, Gabriel Oliveira; de Holanda, Tatiane Bárbara; Lino, Adan Santos; Thomaz Júnior, José Ricardo; Azevedo, José Paulo Soares; Torres, João Paulo Machado (Orbital: The Electronic Journal of Chemistry, 2018)
Water bodies can be considered the ultimate receptor of pollutants produced or remobilized as a result of anthropogenic activities. Whereas diffuse pollution occurs throughout the Piabanha river basin, the aim of this work was to evaluate the distribution of trace elements and persistent organic pollutants in its sediments over time and space, gathering information to assess the risks to the ecosystem and the population. And also to provide data to orient governmental institutions management of water resources in this region. The levels of organic pollutants highlight the influence of the historical use of pesticides in farming and industrial activities, mainly for Posse (203.36 ng/g dry weight) and Fagundes river (198.33 ng/g d.w) during the dry season and Moura Brazil (77.50 ng/g d.w) and Garagem (77.06 ng/g d.w) in the rainy season. In relation to available trace elements, the most contaminated locations were within and around Petrópolis center, possibly by industrial and domestic effluents, where Liceu (44-245 µg/g d.w) and Garagem (15-189 µg/g d.w) showed the highest concentrations of zinc. Furthermore, Liceu (5-58 µg/g d.w) also excelled in concentrations of lead. Cadmium was the element with major contribution to the contamination of the locations studied (Geoaccumulation index from 3 to 5 in all collected points), mainly because of its high mobility and the river flow. In addition, Poço do Ferreira river presented trace elements levels that exceeds the level 2 of the National Environment Council (CONAMA) classification. The authors highlight the need for a monitoring program on this region for the contaminants analyzed.DOI: http://dx.doi.org/10.17807/orbital.v10i4.1084